Basal plane dislocation dynamics in highly p-type doped versus highly n-type doped SiC - Wellmann, Peter; Queren, Desiree; Müller, Ralf; Sakwe, Aloysius; Künecke, Ulrike (Materials Science Forum, 2006)
The long term performance of today's Sic based bipolar power devices suffer strongly from stacking fault formation caused by slip of basal plane dislocations, the latter often originating from the n-type doped Sic substrate wafer. In this paper, using sequentially p-type/n-type/p-type doped Sic crystals, we address the question, whether basal plane dislocation generation and annihilation behaves differently in n-type and p-type Sic. We have found that basal plane dislocations are absent or at least appear significantly less pronounced in p-type doped Sic, which may become of great importance for the stacking fault problem in si
Keywords: p-type SiC; dislocations; stacking faults; bipolar devices